Tanfīż Istirātījiyyah Numbered Heads Together (NHT) li Tarqiyah Nata'ij at-Ta'līm fī Mawdhu' al-Lugah al-'Arabiyyah : Implementing the Numbered Heads Together (NHT) Strategy to Upgrade Learning Outcomes in the Arabic Language - Zainal Abidin; Agus Yasin (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2024)
The Numbered Heads Together (NHT) strategy is one of the learning models of Cooperative Learning. The Numbered Heads Together strategy can increase student activity in the classroom, affecting student learning outcomes. Darul Fikri Islamic Institute is an Islamic educational institution affiliated to Darul Fikri Bringin, Kauman, Ponorogo, which combines two curricula, They are the curriculum of the Ministry of Religious Affairs and the curriculum of the Modern Islamic Institute Gontor Institute in the development of foreign languages, namely Arabic and English. Especially in Arabic subjects, teachers use the lecture method that makes students feel bored and inactive during the learning process in the classroom, affects student activity in the classroom, and makes student learning outcomes low with a grade point below KKM. In addition, in daily activities, students do not use Arabic vocabulary (conversation). Thus, there must be improvements and changes in the learning process using the Numbered Heads Together. Keywords: Learning Outcomes, Numbered Heads Together, Strategy ملخص معهد دار الفكر الإسلامية هي مؤسسة تعليمية إسلامية تابعة لمؤسسة دار الفكر برينجين، كومن، فونوروكو التي تجمع بين منهجين، هما: منهج الوزير الشؤون الدينية والمنهج الدراسي لمعهد دار السلام كونتور  في تطوير اللغات الأجنبية، وهي العربية والإنجليزية. خاصة في المواد العربية، يستخدم المعلمون طريقة المحاضرة التي تصبح الطلاب يشعرون بالملل ونقيص النشاط أثناء عملية التعلم في الفصل وتؤثر على نشاط الطلاب في الفصل وتجعل نتائج تعلم الطلاب منخفضة بمعدل درجات أقل من KKM. بالإضافة إلى ذلك، في الأنشطة اليومية، لا يستخدم الطلاب المفردات العربية (المحدثة). وبالتالي، يجب أن تكون هناك تحسينات وتغييرات في عملية التعلم باستخدام إستراتيجيةNumbered Heads Together Numbered Heads Together الكلمات المفتاحية: نشاط تعلم، نتائج تعلم، الإستيراتيجية